FINANCIAL LITERACY ON POSTGRADUATE STUDENTS TRISAKTI UNIVERSITY - Farah Margaretha; Yosephin Artiani (Business and Entrepreneurial Review, 2015)
financial literacy is a basic need for everyone to avoid financial problems. Understanding of financial literacy is the vital things to obtain a prosperous life and quality. This study was performed to obtain the relationship between financial literacy by gende, age, course of study, income level, employment structure, areas of works, workplaces, and location of residence. Object the research was Trisakti University Postgraduate Students who were already working. This research raised problems concerning gender, age, education, income, natures of work, the workplaces, and residence affecting financial literacy in students of Trisakti University post-graduate program who were employee worked in a variety of fields, where in this research financial literacy was the dependent variable and gender, age, income, nature of works, work place and residence were as independet variables. The researchused 311 primary data optained by questionnaire and then analyzed by using ANOVA in SPSS. This research proposed recommendations so that the University can provide education concerning personal finance to the students so that they from an early age have knowledge concerning personal finance. Financial companies may provide financial literacy to people which were corporate social responsibility.